Origins of Nationality in South Asia - "Bayly, C A" (New Delhi, 2003)
A consideration of the ideological and institutional antecedents of mature Indian nationalism which argues that patriotism is a useful concept with which to understand India in the eighteenth and early nineteenth centuries. Essays on Swadeshi, Indian resistance, and communalism are included in the text.
Keywords: Nationalism